HAMBATAN DAN STRATEGI KOMUNIKASI ANTARPRIBADI PEKERJA SOSIAL DI PANTI PELAYANAN SOSIAL WANITA â€œWANODYATAMAâ€ SURAKARTA - Pahlevi, Nadia Rizky (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2018)
Based on the results of research and analysis that have been done, it can be concluded that the interpersonal communication barrier faced by Peksos at PM in thedominant Women's Institution